Institutional Interactions Processes Modeling in Consumer Cooperatives in the Frameworks of Transaction Theory of Incomplete Contracts as a Social Marketing Tool Realization - TERNOVSKY, Denis S.; PRIZHIGALINSKAYA, Tatiana N.; UKOLOVA, Lyubov' V.; DAVNIS, Valery V.; LAVROVA, Yulia S. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The article is dedicated to the problem of modeling external and internal institutional interactions emerging in the process of economic and social activity of consumer cooperatives with the view of improving social marketing realization on the basis of the simulation of contracting processes. The article provides the specification of shareholders’ and general public contracting models in the process of production of exclusive and inclusive public goods in a consumer cooperative. The article states theoretical dependence between the level of cooperation while producing exclusive goods and differentiation of the general public by the income level, which determines economic and social inefficiency of contract relations. The article proves the possibility of inclusive public goods production and the achievement of Pareto’s efficiency in the distribution of income with the simultaneous production of inclusive public goods in the form of services and exclusive goods in the form of cooperative ideology adherence as a highly specific asset. On the basis of the developed models the article substantiates the peculiarities of social marketing in consumer cooperation organizations through the integration of the relations marketing concept and transaction approach to the organization’s activity; proves the possibility of the dual consideration of costs for the realization of socio-ethical marketing as transaction expenses for the maintenanceof cooperative ideology and transformation expenses on social activity and singles out the directions of consumer cooperatives’ social activity aimed at their external and internal environment and ensuring the involvement of the interested persons in the system of internal contracts.